KAJIAN PUPUK BERSUBSIDI DI PEKALONGAN (Studi Kasus di Kecamatan Kesesi) - Ardiyanto, Wahyu; Budi Santoso, Purbayu (Diponegoro Journal of Economics, 2013)
This study aims to assess the effectiveness of the fertilizer subsidy policy to support rice production with a case study on Kesesi District Pekalongan. Sampling method using purposive sampling where the selection of respondents based on consideration of the research supporting data. The research sample is the entire village in the district by the number of respondents Kesesi 100 farmers. Determination of the number of respondents is based on calculations using formulas Slovin. The analytical method used is descriptive qualitative and quantitative methods, and methods of descriptive statistics. Descriptive qualitative and quantitative methods are used to measure the effectiveness of the fertilizer subsidy policy by using two main indicators, namely the right price and the right amount. While the descriptive statistical method used to determine the proportion of the various financing farmers in one growing season and to determine the amount of net income received by farmers in a single growing season.Results of this study showed that the fertilizer subsidy policy is considered not effective based on the price of subsidized fertilizer level retailers, the results showed 72.19 percent of farmers buy fertilizer at a price above the prevailing HET. Later than HET in terms of the use of fertilizers by farmers are also not in accordance with the recommendations of balanced fertilization. Penelititan results showed 62 percent of farmers use fertilizer farmers are still under the recommendation and 12 percent above the recommended recommendations. It can affect farmers' expenditure, in which case the proportion of research expenditure in the amount of fertilizer farmers 11 percent. These expenses are the second largest expense after labor expenses, it will indirectly affect the income of farmers. Amount of expenditure will reduce the amount of revenue that would diiterima farmers. Based on our research the average net income once the growing season of 100 respondents with an average of 3350,1 mÂ² of land amounting to Rp 3,899.585.